Karakterisasi jenis mineral magnetik sedimen Gua Di Gua Liang Luar Kabupaten Manggarai Barat Provinsi Nusa Tenggara Timur menggunakan metode X-Ray Diffraction (XRD) - Daris Maradelta (PILLAR OF PHYSICS, 2016)
The investigation types of  magnetic minerals cave sediment in Liang Luar Cave Kabupaten Manggarai Barat Provinsi Nusa Tenggara Timur using X-Ray  Diffraction. The  measurement results in the form of  diffraction  angle (2θ), the distance between the field (dhkl), diffraction intensity (I) and relative intensity. The analysis techniques have been used Hight Score Plus Software analysis and manually. The results of measurement data of cave  sediment samples  in  Liang Luar Cave show that the cave sediment samples containing magnetic minerals. The type of magnetic minerals contained in the cave sediment samples  are magnetite, hematite, maghemite, and ilmenite in the cave sediment samples LS11-C3. This indicates that the inconsistencies type of magnetic minerals in each layer of cave sediment in Liang Luar Cave Kabupaten Manggarai Barat Provinsi Nusa Tenggara Timur. While the grain size of magnetic minerals cave sediment samples in Liang Luar Cave is the single-domain (SD) with a size of ≤ 100 nm